10.55041/IJSREM47483 - DR. JAYANTHI KAMALASEKARAN (INTERNATIONAL JOURNAL OF SCIENTIFIC RESEARCH IN ENGINEERING AND MANAGEMENT, 2025)
Abstract - In an organization, there are multiple departments, and each department has its own payroll section responsible for managing payroll activities. These sections handle various tasks such as data collection and preparation, data entry, updates, monitoring, and reporting. With the rapid growth in mobile technology—including smartphones, tablets, and wearable devices—alongside widespread and affordable internet access and advancements in cooperative networking, people now expect to complete tasks quickly and with minimal effort. They demand fast and seamless access to services. Traditionally, processing an employee's salary manually has been a tedious and time-consuming task. This manual approach can be inefficient and prone to delays. To address these challenges, a new system has been introduced that integrates payroll processing with GPS tracking and image verification. This approach streamlines operations, increases accuracy, and reduces the time required to process payroll. Key Words: monitoring, wearable's, GPS Tracking, image.